(untitled) (Academicia Globe: Inderscience Research, 2025)
The integration of Artificial Intelligence (AI) in agriculture presents a significant opportunity to enhance productivity, optimize resource utilization, and improve the quality of agricultural outputs. AI-driven solutions, such as precision farming, automated monitoring systems, and predictive analytics, enable farmers to make data-driven decisions that lead to increased efficiency and sustainability. By leveraging machine learning algorithms, remote sensing technologies, and Internet of Things (IoT) devices, AI can help detect diseases, optimize irrigation, and enhance crop yield predictions. Furthermore, AI-powered automation reduces labor costs and minimizes human errors, ensuring higher efficiency in agricultural processes. However, challenges such as data accessibility, high implementation costs, and the need for specialized expertise remain barriers to widespread adoption. Despite these challenges, AI continues to revolutionize modern agriculture, paving the way for a more resilient and technologically advanced farming industry.